Fatherhood and Sperm DNA Damage in Testicular Cancer Patients - Paoli, Donatella; Pallotti, Francesco; Lenzi, Andrea; Lombardo, Francesco (Frontiers in Endocrinology, 2018)
Testicular cancer (TC) is one of the most treatable of all malignancies and the management of the quality of life of these patients is increasingly important, especially with regard to their sexuality and fertility. Survivors must overcome anxiety and fears about reduced fertility and possible pregnancy-related risks as well as health effects in offspring. There is thus a growing awareness of the need for reproductive counselling of cancer survivors. Studies found a high level of sperm DNA damage in TC patients in comparison with healthy, fertile controls, but no significant difference between these patients and infertile patients. Sperm DNA alterations due to cancer treatment persist from 2 to 5 years after the end of the treatment and may be influenced by both the type of therapy and the stage of the disease. Population studies reported a slightly reduced overall fertility of TC survivors and a more frequent use of ART than the general population, with a success rate of around 50%. Paternity after a diagnosis of cancer is an important issue and reproductive potential is becoming a major quality of life factor. Sperm chromatin instability associated with genome instability is the most important reproductive side effect related to the malignancy or its treatment. Studies investigating the magnitude of this damage could have a considerable translational importance in the management of cancer patients, as they could identify the time needed for the germ cell line to repair nuclear damage and thus produce gametes with a reduced risk for the offspring.